Serum progranulin level is a novel tool for monitoring disease activity of dermatomyositis with antimelanoma differentiation‐associated protein 5 antibodies - Asami Fujii; Yuki H. Mizutani; Miho Kawamura; Kanako Matusyama; Yoko Mizutani; En Shu; Mariko Seishima (Journal of Cutaneous Immunology and Allergy, 2021)
Abstract Objectives Dermatomyositis (DM) is an autoimmune disease that presents with a wide variety of clinical manifestations. Patients with DM or clinically amyopathic dermatomyositis (CADM) with antimelanoma differentiation‐associated protein 5 (anti‐MDA5) antibodies are frequently associated with interstitial pneumonia, especially rapidly progressive interstitial lung disease. Progranulin (PGRN) is an autocrine growth factor involved in inflammation. Elevated serum PGRN levels have been reported in the patients with systemic lupus erythematosus and rheumatoid arthritis. However, they have not been precisely studied in DM/CADM. We assessed PGRN levels as a potential biomarker for DM/CADM with anti‐MDA5 antibodies. Methods Twenty‐four DM/CADM patients with anti‐MDA5 antibodies, 12 patients without anti‐MDA5 antibodies, and eight healthy volunteers were enrolled. We measured serum PGRN levels and compared them between the anti‐MDA5 antibody‐positive and antibody‐negative groups. They were also measured before and after the start of treatment in anti‐MDA5 antibody‐positive patients. We examined the correlations between serum PGRN levels and laboratory data such as serum KL‐6 and ferritin levels. Results Patients with DM/CADM, especially those with anti‐MDA5 antibodies, had significantly higher serum PGRN levels than healthy individuals. They decreased after the start of treatment. Serum PGRN levels were positively correlated with serum KL‐6 and ferritin levels, and anti‐MDA5 antibody titers. Conclusions This is the first study to show that PGRN levels were significantly elevated in the sera of DM/CADM patients, particularly in those with anti‐MDA5 antibodies. PGRN may be a useful biomarker of disease activity. However, further studies are required to reveal the mechanisms of PGRN in DM/CADM more precisely.